Progression in plant phosphate uptake studies - Munusamy, Umaiyal; Khuzaimah, Zailani; Kong, Sze Ling; Abdullah, Siti Nor Akmar (Malaysian Society for Molecular Biology and Biotechnology, 2022)
Phosphate is an important macronutrient essential for various enzymatic reactions, biological processes and biosynthesis of different compounds in plants. There are multiple factors affecting phosphate uptake such as crop physiology, soil structure and texture, plantation management and environmental conditions. There is no specific solution that can be employed for better phosphate uptake by plants but clearly, sustainable agriculture management facilitated by precision crop assessment could be an effective solution. The ability for a better phosphate uptake by plants and that information will ensure the success of small and big scale farmers role in securing the demand for food by the growing population. Therefore, various approach has been taken to identify the phosphate uptake hence with the help of digitalization, we believe there will be innovated phosphate uptake studies compared to how these were previously carried out. In the next decade, more phosphate uptake information data with seamless accessibility will be available to various users. However, data alone will not be able to produce anything, analysis and advisory services are required in helping farmers to use and apply those obtained information for subsequent application in the field. Software applications with advance machine learning will customized the interactions between devices and data for the user. As they interact, they provide an untapped opportunity for better farm decision-making in real time. In this review, we will discuss how digitalization has improved to change the overall plant phosphate uptake studies and by what means the generated information can be efficiently utilized by the farmers and the various stakeholders.